Reply to Comment by Zhang et al. on the Paper "Long‐Term Variations of Exospheric Temperature Inferred From foF1 Observations: A Comparison to ISR Ti Trend Estimates" by Perrone and Mikhailov. Issue 10 (27th October 2018) - Perrone, L.; Mikhailov, A. V.
Abstract: The majority of Zhang et al. critical comments concern our method to retrieve aeronomic parameters from ionosonde f o F 1 observations. The main idea of the method was described by Mikhailov and Perrone (2016, https://doi.org/10.1002/2016JA022716 ), but it is seen that an additional clarification is required. The method has been slightly changed to meet numerous comments of referees, and its description is given here. The comments by Zhang et al. are analyzed and answered. Key Points: An improved method to extract a self‐consistent set of seven aeronomic parameters responsible for the midlatitude F 1 region formation is presented Mean ion mass inferred from f o F 1 observations manifests negative trends that should correspond to Tn negative trend contrary to ISR results Routine ISR method based on a fixed model of ion composition (crucial for the method) should inevitably result in wrong Tn long‐term trends